2021
DOI: 10.1097/brs.0000000000004169
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Cohort Analysis of Drain Usage in Elective Anterior Cervical Discectomy and Fusion

Abstract: Study Design. This is a retrospective, cohort analysis of multiinstitutional database.Objective. This study was designed to analyze the impact of drain use following elective anterior cervical discectomy and fusion (ACDF) surgeries. Summary of Background Data. After ACDF, a drain is often placed to prevent postoperative hematoma. However, there has been no high quality evidence to support its use with ACDF despite the theoretical benefits and risks of drain placement. Methods. The Michigan Spine Surgery Improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…demonstrated that the placement of percutaneous drainage increased the length of hospital stay [8]. Therefore, some studies argue that the use of drains would be unnecessary due to the low frequency of complications of these approaches [1,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the placement of percutaneous drainage increased the length of hospital stay [8]. Therefore, some studies argue that the use of drains would be unnecessary due to the low frequency of complications of these approaches [1,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%